Coverage of recommended vaccines during pregnancy in Flanders, Belgium. Fairly good but can we do better?. Issue 19 (3rd May 2018) - Maertens, Kirsten; Braeckman, Tessa; Blaizot, Stéphanie; Theeten, Heidi; Roelants, Mathieu; Hoppenbrouwers, Karel; Leuridan, Elke; Van Damme, Pierre; Vandermeulen, Corinne
Abstract: Background: In Flanders, Belgium, pertussis vaccination is recommended since 2013 and available free-of-charge in every pregnancy between 24 and 32 weeks of gestation. Influenza vaccination is recommended for more than 10 years with a co-payment system in the second or third trimester of pregnancy, when pregnancy coincides with the influenza season. This study aims to estimate the coverage of pertussis and influenza vaccination during pregnancy in 2016 and to determine predictors for missing vaccination. Methods: Postpartum women were visited at home for a vaccination coverage survey using an Expanded Program on Immunization (EPI)-based two-stage cluster sampling design. Predictors for missed vaccination were identified using a multiple logistic regression model. Results: Among 481 participating women, 69.3% were vaccinated against pertussis and 47.2% were vaccinated against influenza. Moreover, 65.3% of pertussis vaccine recipients and 96.9% of influenza vaccine recipients were vaccinated within the recommended gestational window. Surprisingly, among women who were completely informed (i.e. on disease-associated risks, maternal vaccination costs and recommendations), still 12.4% were unvaccinated against pertussis and 23.9% against influenza. In the final models, the only common predictor of missing maternal pertussis and influenza vaccination was multiparity. Significant predictors of maternal pertussis vaccination were family income (less likely if unknown or low (< €3000) than if moderate (€3001-€4000)) and hospital of delivery (less likely if >800 annual deliveries than <800). Significant predictors of maternal influenza vaccination, though with less straight-forward associations, were maternal ethnicity and educational level, involvement of a gynaecologist in pregnancy follow-up, and characteristics of the hospital of delivery. Conclusion: In Flanders, more than two-third of pregnant women receives pertussis vaccination but less than half of them receives the influenza vaccine. Further improvement for both maternal vaccination programs can be achieved by targeting the underserved populations and diminishing vaccination hurdles.